Microbial production of lactic acid: the latest development. (1st November 2016) - Juturu, Veeresh; Wu, Jin Chuan
Abstract: Lactic acid is an important platform chemical for producing polylactic acid (PLA) and other value-added products. It is naturally produced by a wide spectrum of microbes including bacteria, yeast and filamentous fungi. In general, bacteria ferment C5 and C6 sugars to lactic acid by either homo- or hetero-fermentative mode. Xylose isomerase, phosphoketolase, transaldolase, l - andd -lactate dehydrogenases are the key enzymes that affect the ways of lactic acid production. Metabolic engineering of microbial strains are usually needed to produce lactic acid from unconventional carbon sources. Production ofd -LA has attracted much attention due to the demand for producing thermostable PLA, but large scale production ofd -LA has not yet been commercialized. Thermophilic Bacillus coagulans strains are able to producel -lactic acid from lignocellulose sugars homo-fermentatively under non-sterilized conditions, but the lack of genetic tools for metabolically engineering them severely affects their development for industrial applications. Pre-treatment of agriculture biomass to obtain fermentable sugars is a pre-requisite for utilization of the huge amounts of agricultural biomass to produce lactic acid. The major challenge is to obtain quality sugars of high concentrations in a cost effective-way. To avoid or minimize the use of neutralizing agents during fermentation, genetically engineering the strains to make them resist acidic environment and produce lactic acid at low pH would be very helpful for reducing the production cost of lactic acid.